Supervisi Klinis oleh Kepala Sekolah guna Meningkatkan Kompetensi Guru dalam Mengelola Administrasi Kelas di SD Negeri 42 Ampenan - Tri Wahyuni (Jurnal Paedagogy, 2021)
This study aims to improve the ability of teachers to organize their classes, improve teacher professionalism in carrying out their main tasks and functions as teaching staff, increase teacher insight and knowledge about teacher competencies and improve the quality of teachers in managing classroom administration through clinical supervision. This research method uses school action research. The subjects in this study were 13 teachers of SD Negeri 42 Ampenan. Data collection techniques using observation, interviews, and documentation. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results of this study indicate that the ability of teachers to manage classroom administration can be improved by providing clinical supervision.